Introducing the New Surgical Robot HUGO™ RAS: System Description and Docking Settings for Gynecological Surgery - Gueli Alletti, Salvatore; Chiantera, Vito; Arcuri, Giovanni; Gioè, Alessandro; Oliva, Riccardo; Monterossi, Giorgia; Fanfani, Francesco; Fagotti, Anna; Scambia, Giovanni (Frontiers in Oncology, 2022)
This paper aims to provide a detailed description of the new HUGO RAS System and suggest docking settings for gynecological surgery. The system is composed of an "open" surgical console with an HD-3D passive display, a system tower, and four arm carts. Each arm has an extreme range of adaptability resulting from the numerous joints. The human cadaver labs were performed at the ORSI Academy between August and December 2021. All the procedures were performed by two surgical equipes, each composed of a high-volume surgeon experienced in robotic surgery, gynecologic oncology, pelvic sidewall surgery, and one bed-side assistant. Three main gynecological surgical scenarios were identified: standard pelvic surgery, pelvic sidewall surgery, para-aortic/upper abdominal surgery. Concerning the port placement, the chosen options were called "straight" and "bridge"; instead, the so-called "compact" and the "butterfly" configurations were identified for the arm cart positioning. Four cadavers were used to perform a total hysterectomy, radical hysterectomy, pelvic exenteration, pelvic and para-aortic lymphadenectomy, and omentectomy. We performed several tests aimed to identify the best system configurations to draw the proper efficiency by system’s flexibility in all gynecological surgical scenarios. The straight port placement seems to be adequate standard pelvic surgery. The bridge trocar position is better to reach the female pelvis's deeper and lateral anatomical regions. The compact and the butterfly arm carts allocations are adequate for both the straight and the bridge port placement. When a deep pelvic surgery was going to be performed, the bed-side assistant was more proficient by working with a standard laparoscopic instrument from an ancillary port placed in the left iliac fossa. The arm carts needed to be moved in an open manner like for the proposed butterfly configuration. On the contra, the compact disposition left enough space to assist from a Palmer's point port. Several basic and advanced gynecological surgical procedures were performed and completed successfully without encountering any technical or surgical issue: the results obtained were judged sufficient to proceed with the clinical experience in daily practice. The HUGOTM RAS system has proved to be flexible and highly performing in various surgical scenarios.